2018
DOI: 10.1021/acschembio.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Production and Purification of a Functional Chloroform Reductive Dehalogenase

Abstract: Reductive dehalogenases (RDases) are key enzymes involved in the respiratory process of anaerobic organohalide respiring bacteria (ORB). Heterologous expression of respiratory RDases is desirable for structural and functional studies; however, there are few reports of successful expression of these enzymes. Dehalobacter sp. strain UNSWDHB is an ORB, whose preferred electron acceptor is chloroform. This study describes efforts to express recombinant reductive dehalogenase (TmrA), derived from UNSW DHB, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…Hence, a host organism for heterologous production had to be found that provided both an adequate amount of Cbas and iron-sulfur clusters for RDase assembly. In recent years, the Cba-producing gammaproteobacterium Shimwellia blattae (Lawrence and Roth, 1996) and the Gram-positive Bacillus megaterium (Wolf and Brey, 1986) were successfully applied (Mac Nelly et al, 2014;Payne et al, 2015;Kunze et al, 2017;Jugder et al, 2018). B. megaterium synthesizes the standard-type B 12 cofactor (5,6-dimethylbenzimidazolyl-Cba), and S. blattae produces pseudo-B 12 (adeninyl-Cba) de novo (Wolf and Brey, 1986;Mac Nelly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a host organism for heterologous production had to be found that provided both an adequate amount of Cbas and iron-sulfur clusters for RDase assembly. In recent years, the Cba-producing gammaproteobacterium Shimwellia blattae (Lawrence and Roth, 1996) and the Gram-positive Bacillus megaterium (Wolf and Brey, 1986) were successfully applied (Mac Nelly et al, 2014;Payne et al, 2015;Kunze et al, 2017;Jugder et al, 2018). B. megaterium synthesizes the standard-type B 12 cofactor (5,6-dimethylbenzimidazolyl-Cba), and S. blattae produces pseudo-B 12 (adeninyl-Cba) de novo (Wolf and Brey, 1986;Mac Nelly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…UNSWDHB. It was chosen because it was previously expressed in its active form in B. megaterium (35). TmrA was cloned without its TAT signal peptide into the p15TV-L expression vector.…”
Section: Resultsmentioning
confidence: 99%
“…One advantage is higher protein yields in E. coli . From 1 L of culture, we were able to obtain approximately 2 mg of TmrA whereas to get 0.9 mg of TmrA at a similar purity, 15 L of B. megaterium was required (35). Furthermore, the RDase expression vectors can be commercially produced in typical pET vectors while those for B. megaterium and S. blattae generally have to be manually cloned (33, 35, 36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations